Does Laterality of Lower Extremity Donor Site Affect Outcomes in Microvascular Soft Tissue Lower Extremity Reconstruction? - Yu, Jason W.; Rifkin, William J.; Lee, Z-Hye; Borab, Zachary; Alfonso, Allyson R.; Thanik, Vishal D.; Levine, Jamie P. (Journal of Reconstructive Microsurgery, 2020)
Background There are many different variables to consider in lower extremity microvascular soft tissue reconstruction including flap choice. Our aim is to objectively evaluate recipient complications related to lower extremity donor flap laterality.Methods A total of 77 lower extremity soft tissue reconstructions utilizing microvascular free tissue transfers for Gustilo type III between 1979 and 2016 were collected. We compared complication rates between ipsilateral and contralateral donor sites relative to the injured leg. The following parameters were analyzed: overall complications, total flap failure, partial flap failure, major complications, operative takebacks, and salvage rates.Results In this study, 25 ipsilateral reconstructions were performed, while 52 cases utilized the contralateral leg. Overall complication rates were higher in the ipsilateral group (40.0%) compared with the contralateral side (23.1%) but were not statistically significant (p = 0.12). The ipsilateral group was four times as likely to experience vascular compromise (24.0 vs. 5.8%; p = 0.05). However, there were no significant differences in complications, flap failures or flap survival. Mean operative time was significantly greater in the same side group as compared with the contralateral group (11.3 vs. 7.5 hours; p = 0.006).Conclusion Although there is a higher risk of anastomotic thrombosis, particularly venous thrombosis, associated with ipsilateral donor-site group, there were no significant differences in complications or flap survival. Flaps can be harvested from a traumatized leg with acceptable complication rates while avoiding the morbidity of operating on an uninjured limb.
Keywords: donor site; lower extremity reconstruction; free flaps